2018
DOI: 10.1039/c8nr00020d
|View full text |Cite|
|
Sign up to set email alerts
|

Hierarchically structured iron-doped silver (Ag–Fe) lotus flowers for an efficient oxygen reduction reaction

Abstract: The development of cheap and efficient electrocatalysts for the oxygen reduction reaction (ORR) is vital for the immediate commercialization of fuel cells which are still limited by the high cost and low performance of the utilized commercial Pt-based electrodes. As a promising alternative, this study reports on the synthesis of hierarchical iron-doped silver lotus flowers (AgFelotus) by a facile chemical procedure as robust and efficient ORR electrocatalysts. Succinic acid was used as a structure directing ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…As clearly shown in this figure, AgFe amaranth maintains its structure and the morphology after hydrogen peroxide electrolysis. It is worth mentioning here that two new diffraction peaks appeared after hydrogen peroxide reduction in alkaline medium which are attributed to FeOOH, see inset of Figure B.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…As clearly shown in this figure, AgFe amaranth maintains its structure and the morphology after hydrogen peroxide electrolysis. It is worth mentioning here that two new diffraction peaks appeared after hydrogen peroxide reduction in alkaline medium which are attributed to FeOOH, see inset of Figure B.…”
Section: Resultsmentioning
confidence: 85%
“…As shown in Figure A–F, the concentration of the directing agent has a significant effect on the morphology of the obtained silver particles. Without using malonic acid, silver particles with ball-like structures were observed with ∼2 μm ball diameter (Figure A), while using low malonic acid concentration (∼0.2 mM) resulted in the formation of small buds (with ∼90 nm average particle size, as estimated from its respective XRD pattern using the Scherrer equation) , on their surfaces, which we called craspedia-globosa flowers (Figure B). Those created buds developed with a further increase in the malonic concentration, where the addition of 0.5 mM malonic acid led to the appearance of silver particles with a chrysanthemum flower-like structure composed of intersected sheets with a ∼72 nm average particle size (Figure C).…”
Section: Resultsmentioning
confidence: 99%
“…By comparison to literature concerning the application of nanostructured Agbased catalysts for oxygen reduction in alkaline media, it can be concluded that AgFeCN x /GNP800-C has comparable performance relative to such materials as Ag 4 Sn/Vulcan [38], CoOx-Ag/rGO [34], Ag/GO/C [62], Ag/rGO [63], and to some Vulcan-supported Ag nanoparticles [9,64,65]. On the other hand, the activity has been still lower than that characteristic of FeAgPc/KB(600) [37], AgFe lotus /Vulcan [40], and Ag/N-rGO [66] systems. Nevertheless, precise comparison of performances of various catalysts reported in literature is rather difficult, due to differences in morphologies and textures of supports, shapes and sizes of nanoparticles, loadings of catalysts, compositions of electrolytes, and their concentrations.…”
Section: Gnp800mentioning
confidence: 97%
“…When it comes to structural dependence of the oxygen reduction kinetics, it tends to increase according to the following order of planes: (100) < (111) < (110) [31]. It is also noteworthy that fairly active and stable materials have been obtained by combining silver with manganese oxides [32,33], cobalt oxides [34], molybdenum oxides [35], and other transition metals (Co, Cu, Ni, Sn, Fe) [36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Individual nanoplates are composed of merging, rugged nanobelts (Figure B) and possess {111} basal planes and numerous in‐plane stacking faults, which surface at their edges (Figure S4 in the Supporting Information). If desired, the adsorbed Fe(III) complex can be easily removed in neutral or acidic environment (Figure S5 in the Supporting Information), albeit Fe‐doped Ag nanostructures can show catalytic synergy …”
mentioning
confidence: 99%